(untitled) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2025)
The article examines the formation of the patrimony of the monasteries of Santa Maria di Licodia and San Nicolò l’Arena in Sicily, moving from the analysis of three unpublished privileges granted by the Aragonese sovereigns between 1336 and 1361. The study is based on documents preserved in the Tabulario of the ‘venerable monasteries’, which reveal the strategies adopted by the monks to protect and expand their land holdings through royal privileges, deeds of gift, purchases and sales, permutations and testamentary bequests. The privileges studied include a letter from King Peter II settling a dispute over an olive grove; a privilege from Infante Giovanni confirming a land donation; and a ratification from Queen Constance of Aragon on a land exchange. Not only do these documents illustrate the economic transactions carried out by the monks, but they also offer insight into the political and religious interests of the Aragonese rulers, the internal dynamics of the Sicilian aristocracy, and relations with the local notables. The article thus attempts to contribute to the understanding of the historical and socio-economic dynamics of Aragonese Sicily and the formation of the large monastic estates on the southern slope of Etna in the 14th century.